M.NÍZANOV ShÍǴARMALARÍNDA FRAZEOLOGIZMLERDIŃ DÁSTÚRIY QOLLANÍW ÓZGEShELIGI - Reymova, Xurziya Jaqsılıq qızı; Saparmatov, Omar Shamurat ulı (SCIENCE and SOCIETY, 2026)
This article analyzes the specific features of using phraseological units in the works of a talented representative of Karakalpak literature. In particular, the author highlights the constant use of stable expressions existing in the vernacular, their role in enriching the content of the literary text, and their significance in creating an image. During the study, the functions of phraseological units in preserving national flavor, enhancing the naturalness of characters' speech, and enhancing the expressiveness of the work were demonstrated through examples. The artistic and aesthetic function of folk expressions and traditional phrases in the writer's style is also scientifically evaluated.